Efeitos de temperatura da atmosfera por simulação de múons de raios cósmicos - Tognini, Stefano Castro (2012)
The collision between a cosmic ray and an atmosphere nucleus produces a set of secondary particles, which will decay or interact with other atmosphere elements. This set of events produced a primary particle is known as an extensive air shower (EAS) and is composed by a muonic, a hadronic and an electromagnetic component. The muonic flux, produced mainly by pions and kaons decays, has a dependency with the atmosphere’s e↵ective temperature: an increase in the e↵ective temperature results in a lower density profile, which decreases the probability of pions and kaons to interact with the atmosphere and, finally, resulting in a major number of meson decays. This dependency between the muon flux and the atmosphere’s e↵ective temperature can be written as !Rμ/hRμi = ↵T!Teff/hTeff i, where the ↵T coefficient was measured by a set of experiments such as AMANDA, Borexino, MACRO and MINOS. This research will verify this temperature e↵ect by simulating the final muon flux produced by two di↵erent parameterizations of the atmospheric model. Each parameterization is described by a depth function X(h), which can be related to muon flux by the form !Rμ/Rμ = ↵X!X/X. This relation, associated with the MINOS experimental value for ↵T = 0.873±0.009, is used to define the relation between !X/X and !Teff/hTeff i. The simulation is done by using a set of high and low energy hadronic interaction and decay models called CORSIKA. All parameters were defined in order to fit the physical characteristics of the MINOS’ Far Detector and, by using its experimental value for ↵T , the results show that a variation of ⇠2.5% in X(h) implies in a variation of ⇠1% in Teff . Moreover, it is shown that the simulation is qualitatively in agreement with all physical behaviors expected from an increase in the value of the e↵ective temperature of the atmosphere. The values found for ↵X = 0.31+0.12 −0.16 and ↵X = 0.30+0.12 −0.16, which represent the results for the correlation with and without the selection cuts for the Far Detector, suggest that there is no dependency between the particles’ energy and its interaction probability within the investigated energy range.